Helicobacter pylori Eradication with Either Seven-Day or 10-Day Triple Therapies, and with a 10-Day Sequential Regimen - Giuseppe Scaccianoce; Cesare Hassan; Alba Panarese; Donato Piglionica; Sergio Morini; Angelo Zullo (Canadian Journal of Gastroenterology, 2006)
BACKGROUND: Helicobacter pylori eradication rates achieved by standard seven-day triple therapies are decreasing in several countries, while a novel 10-day sequential regimen has achieved a very high success rate. A longer 10-day triple therapy, similar to the sequential regimen, was tested to see whether it could achieve a better infection cure rate.